DEVELOPMENT AND CHARACTERIZATION OF PH-RESPONSIVE POLYMERIC MICROBEADS INTERCALATED WITH MONTMORILLONITE FOR CONTROLLED RELEASE OF DOXORUBICIN - RATHNAM, S. RANGA; REDDY, O. SREEKANTH; PATWARI, S. B. (International Journal of Applied Pharmaceutics, 2023)
Objective: The aim of the present study is to develop pH-responsive polymeric microbeads for controlled release of doxorubicin. Methods: Doxorubicin-encapsulated polymeric microbeads were developed by a simple ionotropic gelation method using sodium alginate, gum ghatti, and montmorillonite (MMT). In this work, we investigate the positive benefits of MMT mineral as a drug carrier for the controlled release of DOX. X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, and scanning electron microscopy (SEM) were used to characterize the generated microbeads. The influence of hetero-ionic concentration on drug encapsulation efficiency and drug release from microbeads was examined. In vitro release and swelling studies were performed at pH 2.0 and 7.4 at 37 °C. The cytotoxicity of the developed microbeads was studied using in vitro cultures of the human breast cancer cell line (MCF-7). Results: FTIR confirms the generation of microbeads and also the interaction between the polymer matrix, DOX and MMT clay. XRD analysis reveals the molecular dispersion of DOX and the presence of MMT in the polymeric matrix. SEM studies reveal the developed microbeads are spherical in shape with rough surfaces. Swelling and in vitro release studies are dependent on the pH of the test medium, which may be favorable for intestinal drug delivery. MTT results reveal that the developed microbeads showed good in vitro toxicity against MCF-7 cells. The drug release kinetics of the generated microbeads are followed by both the higuchi and korsmeyer-peppas models. Conclusion: The findings suggest that the DOX-encapsulated microbeads are promising carriers for drug delivery applications. The fabricated microbeads further needs warrant for drug delivery applications.